Housing policies beyond numbers: A comparative study in Portugal and Italy - Di Giovanni, C. F. (2019)
The paper analyses how housing is structured in Portugal and Italy, focusing in particular on the recent housing policies. The objectives are: a) discuss the legislative solutions adopted in the last years to solve the housing needs; b) show the epistemological difference for the concept of social housing; c) compare the institutional variations, namely, the relevance of the local, regional and central levels. Despite Portugal and Italy having the same percentage of social housing and common characteristics of Southern Europe countries, we find differences comparing housing policies and how the countries deal with social housing. The methodology is organized into: i) bibliographic review; ii) analysis of the principal statistic data; iii) analysis of the legislation; iv) interviews with public decision-makers. Notwithstanding a wide literature about housing studies in Northern countries and comparing North and South housing policies approaches, few studies focus on the comparison between Southern European countries. For this reason, the research seeks to increase the knowledge about the singularities of the South and thus contributing to the construction of a theoretical approach South-inspired.